Optimalisasi ChatGPT sebagai Asisten Digital untuk Membantu Siswa Madrasah Ibtidaiyah Al Khoiriyah dalam Menyelesaikan Tugas dan Meningkatkan Pemahaman Materi - Nawangsih, Ismasari; Majid, Annisa Maulana; Maulana, Donny; Purnamasari, Pupung; Rahardjo, Sugeng Budi (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
Community service aims to optimize the use of ChatGPT as a digital assistant in helping Madrasah Ibtidaiyah (MI) Al Khoiriyah students complete assignments and improve understanding of subject matter. ChatGPT, as a form of artificial intelligence technology, has the potential to provide interactive and responsive assistance in learning, which can be tailored to student needs. Through a technology-based approach, ChatGPT is expected to be able to provide clear explanations, help solve questions, and provide constructive feedback for students. This research uses qualitative methods with direct observation and interviews with teachers and students of MI Al Khoiriyah. The research results show that using ChatGPT can increase effectiveness in the learning process, especially in terms of understanding material and completing assignments. Thus, ChatGPT has the potential to be an effective tool in supporting education at the elementary level, especially for Madrasah Ibtidaiyah students.